Current Concepts in the Management of Dupuytren Disease of the Hand. Issue 11 (1st June 2021) - Gil, Joseph A.; Akelman, Matthew R.; Hresko, Andrew M.; Akelman, Edward
Abstract : Dupuytren disease is a fibroproliferative disorder of the palmar fascia of the hand. Little agreement and remarkable variability exists in treatment algorithms between surgeons. Because the cellular and molecular etiology of Dupuytren has been elucidated, ongoing efforts have been made to identify potential chemotherapeutic targets that could modulate the phenotypic expression of the disease. Although these efforts may dramatically alter the approach to treating this disease in the future, these approaches are largely experimental at this point. Over the past decade, the mainstay nonsurgical options have continued to be percutaneous needle aponeurotomy and collagenase Clostridium hystoliticum, and the most common surgical option is limited fasciectomy.